Quality of springs water and resistance profile of aerobic bacteria to antimicrobials under different land-use areas in the José Pereira River micro-basin (Itajubá – MG, Brazil) - Rogério Melloni; Brenda Mayra Fernandes de Carvalho; Mariléia Andrade; Karina da Costa Sassi Bortoloti; Paulo Sérgio Marques (Ambiente)
There have been common reports of antibiotic-resistant bacteria in natural environments, mainly due to the indiscriminate use and disposal of these agents. Especially in rural areas, people frequently use water from springs and other natural sources, and the water quality is often unknown. The present study evaluates water quality (physical, chemical and microbiological) and the resistance profile of aerobic bacteria to 10 antibiotics in springs from areas comprising varying land-use systems, in the José Pereira River micro-basin, Itajubá (MG). Samples were collected from 12 springs, during two seasons, the dry and rainy. The water samples of the different springs do not attempt the established standards for human consumption. There was strong influence of season in microbial water quality, with higher average values for aerobic bacteria, Escherichia coli and total coliform bacteria for the rainy season. No relationship as observed between season and bacterial resistance to the antibiotics, despite more strains being resistant to penicillin, and fewer strains resistant to ciprofloxacin, chloramphenicol and gentamicin, independently of land-use surrounding the springs.